Towards the fate of the oscillating false vacuum - Darmé, Luc; Jaeckel, Joerg; Lewicki, Marek (Arxiv, 2017)
Motivated by cosmological examples we study quantum field theoretical tunnelling from an initial state where the "classical field", i.e. the vacuum expectation value of the field operator is spatially homogeneous but performing a time-dependent oscillation about a local minimum. In particular we estimate both analytically and numerically the exponential contribution to the tunnelling probability. We additionally show that after the tunnelling event, the classical field solution - the so-called "bubble" - mediating the phase transition can either grow or collapse. We present a simple analytical criterium to distinguish between the two behaviours.